Perceiving stress on affective state based on features from EEG - Muhd Adnan, Hafizuddin; Yaacob, Hamwira Sakti (IIUM Press, International Islamic University Malaysia, 2017)
The EEG (Electroencephalogram) from brain signal has been broadly used to reveal human affects based on Valence, Arousal and dominance through computational modelling. Recently, less study on EEG been done in detail, directly to reveal and quantify the stress from affects dynamically based on EEG signal. In addition. There is no study currently perform to identify stress from the features based on EEG signals simultaneously. As for the objective of this paper, this study will only try to do features analysis of stress by comparing the statistical features of affects from the data obtained from three subjects. The data was collected during the trial session for new assembled EEG mobile system at Simulation Centre Akademi Laut Malaysia (ALAM). Subjects consist of three marine pilot who were given tasks to navigate ships in the simulated scenes. Findings and observations from the analysis are reported in this paper.